Political Ecology Study: Implementation of Presidential Decree Number. 52 of 1995 About the Jakarta Bay Reclamation and Revitalization - Sambodo, Widodo; Budiastuti, Sri; Setyono, Prabang; Sudarwanto, AL. Sentot (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
The reclamation of the north coast of Jakarta is carried out based on the government policy stipulated in Presidential Decree No.52 of 1995 concerning the Reclamation and Revitalization of the Jakarta Bay policy DKI Regional Government with the issuance of Perda DKI No. 8 of 1995. This research on the implementation of the reclamation policy aims to prove that there are mistakes in implementing the bicycle policy in the form of a Presidential Decree or a DKI regional government's decision. The research method used a qualitative approach by conducting surveys, collecting primary data, interviewing resource persons from the Government, communities, and NGOs. As for the discussion results, the policy's implementation found an impact on the environment, including on the livelihoods of the fishing communities in the vicinity. The results of the evaluation of the reclamation policy of the north coast of Jakarta based on political ecology, for the implementation of Presidential Decree No. 52 of 1995, there is a policy failure because this policy does not consider long-term interests such as the existence of coastal resources and the environment. Meanwhile, Perda DKI No. 8/1995, as a follow-up to Presidential Decree No. 52/1995, can be a failure in its implementation (implementation failure) because it ignores environmental damage socio-economic problems, thus threatening the livelihoods of fishing communities. While the conclusion from the research results there has been a failure of policy formulation (policy failure) and failure of implementation of policies (implementation failure), so that policies in the form of Presidential Decree No. 54 of 1995 and DKI PerDa No 8 of 1995, were the beginning of a mistake in implementing the reclamation of Jakarta Bay which then created a conflict of interest.